Continuous spectrum of glucose dysmetabolism due to the KCNJ11 gene mutation—Case reports and review of the literature. Issue 1 (27th October 2020) - He, Binbin; Li, Xia; Zhou, Zhiguang
Abstract : The KCNJ11 gene encodes the Kir6.2 subunit of the adenosine triphosphate‐sensitive potassium (KATP ) channel, which plays a key role in insulin secretion. Monogenic diseases caused by KCNJ11 gene mutation are rare and easily misdiagnosed. It has been shown that mutations in the KCNJ11 gene are associated with neonatal diabetes mellitus (NDM), maturity‐onset diabetes of the young 13 (MODY13), type 2 diabetes mellitus (T2DM), and hyperinsulinemic hypoglycemia. We report four patients with KCNJ11 gene mutations and provide a systematic review of the literature. A boy with diabetes onset at the age of 1 month was misdiagnosed as type 1 diabetes mellitus (T1DM) for 12 years and received insulin therapy continuously, resulting in poor glycemic control. He was diagnosed as NDM with KCNJ11 E322K gene mutation, and glibenclamide was given to replace exogenous insulin. The successful transfer time was 4 months, much longer than the previous unsuccessful standard of 4 weeks. The other three patients were two sisters and their mother; the younger sister was misdiagnosed with T1DM at 13 years old, while the elder sister was diagnosed with diabetes (type undefined) at 16 years old. They were treated with insulin for 3 years, with poor glycemic control. Their mother was diagnosed with T2DM and achieved good glycemia control with glimepiride. They were diagnosed as MODY13 because of the autosomal dominant inheritance of two generations, early onset of diabetes before 25 years of age in the two sisters, and the presence of the KCNJ11 N48D gene mutation. All patients successfully transferred to sulfonylureas with excellent glycemic control. Therefore, the wide spectrum of clinical phenotypes of glucose dysmetabolism caused by KCNJ11 should be recognized to reduce misdiagnosis and implement appropriate treatment. Abstract : Highlights The KCNJ11 gene encodes the Kir6.2 subunit of the adenosine triphosphate‐sensitive potassium (KATP ) channel, which plays a key role in insulin secretion. Monogenic diseases caused by KCNJ11 gene mutation are rare and easily misdiagnosed. Mutations in the KCNJ11 gene are associated with neonatal diabetes mellitus, maturity‐onset diabetes of the young 13, type 2 diabetes mellitus, and hyperinsulinemic hypoglycemia. We report four patients with KCNJ11 gene mutations and provide a review of the literature. 摘要: KCNJ11 基因编码胰岛β细胞上ATP敏感性钾通道( KATP )的Kir6.2亚基, 是调节胰岛素分泌的重要基因。 KCNJ11 基因突变引起的单基因疾病较罕见, 在临床工作中容易误诊。研究表明, KCNJ11 基因突变不仅可导致新生儿糖尿病(NDM), 还与青少年发病的成人糖尿病13(MODY13)、2型糖尿病(T2DM)、婴儿持续性高胰岛素血症性低血糖症(PHHI)的发生有关。本文报告了4例 KCNJ11 基因突变的患者并对文献进行系统回顾。 病例1是1例病程长达12年, 长期误诊为1型糖尿病(T1DM)而接受胰岛素治疗, 但血糖控制不佳、频发低血糖的糖尿病患者。询问病史发现患者为出生后1月龄起病, 行基因检测明确为 KCNJ11 E322K 基因突变。诊断为NDM, 予以格列本脲成功有效地替代外源性胰岛素治疗, 但转换成功的时间长达4个月, 远长于目前国际所报道的不成功标准4周。其他三例患者为一个家系, 包括两姐妹及其母亲, 先证者为家系中的妹妹, 她在13岁时被诊为T1DM, 同时姐姐在16岁时发现血糖升高, 被诊断为糖尿病(分型待定)。两姐妹使用胰岛素治疗3年, 血糖控制不佳。她们的母亲在36岁时诊断为T2DM, 口服格列美脲取得良好血糖控制。该家系有两代直系亲属患有糖尿病, 且符合常染色体显性遗传规律; 两姐妹均在25岁以前诊断糖尿病, 行基因检测明确存在 KCNJ11 N48D 基因突变。因此被诊断为MODY13。使用格列本脲治疗后, 两姐妹成功脱离胰岛素治疗, 且血糖控制理想。 以上病例提示我们应认识到临床上存在 KCNJ11 基因突变所致不同类型和不同程度的糖代谢异常, 我们需要根据患者疾病特征及时发现, 减少误诊并予以合理的精准治疗。